Rancang Bangun Aplikasi Informasi Biaya Produksi Berbasis Web Di PT.Bimasakti Karya Prima - Sri Rahayu; Irma Kurnia Juliany; Duwi Lailatul Juniar (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2020)
PT.Bimasakti Karya Prima is a company engaged in manufacturing by producing "FANS Indonesia" shoes. Production is the process of converting raw materials to finished goods and adding value to a product. However, the current system is not yet fully able to help, because the making of the Consumption Sheet in the process of material detailing and the Costing process of shoes are on two devices with different operating systems, so the need to re-type the data on the Consumption Sheet in the costing process. The lack of available databases makes it difficult to update data and needs to replace one by one on each sheet. The purpose of this research is to design a web-based Production Cost Information Application, create a database in accordance with company needs that will facilitate data management production costs as well as integrating systems. The research method used is the method of data collection by observing, interviewing and studying literature. The results obtained from this study are a cost information application system that helps companies manage data. Starting from determining the specifications of components and materials for the production of shoes to the costing process.